Effect of bronchodilators on respiratory resistance in infants and young children with bronchiolitis and wheezy bronchitis. Issue 9 (September 1975) - Rutter, N; Milner, A D; Hiller, E J
Abstract : Rutter, N., Milner, A. D., and Hiller, E. J. (1975). Archives of Disease in Childhood, 50, 719. Effect of bronchodilators on respiratory resistance in infants and young children with bronchiolitis and wheezy bronchitis. Respiratory resistance was measured using a forced oscillation technique in 16 infants and young children with bronchiolitis and wheezy bronchitis. Measurements were made before and after administration of nebulized salbutamol or isoprenaline. No significant change in resistance was found.